Perbaikan Kualitas Semen Ayam Kampung Melalui Peningkatan Energi Metabolisme Pakan - Nining Haryuni; Lestariningsih Lestariningsih; Binti Khopsoh (LPPM Universitas Nahdlatul Ulama Blitar, 2022)
This study was intended to obtain feed with the best energy level to improve the quality of native chicken semen. This study is a biological study with 4 levels of metabolic energy (2700; 2750; 2800 and 2850 kcal/kg) using a completely randomized design (CRD) where each treatment was repeated 5 times. Each treatment used 1 native male chicken that was 80 weeks old and in good health. Increasing energy level in feed significantly (p<0.05) increased semen volume; very significant (p<0.01) improved color and increased semen consistency; but not significant (p>0.05) the effect on semen pH. The average volume of semen obtained ranged from 0.45-1.30ml; semen color score 2.25-3.00; semen consistency score 2.25-3.00 and semen pH 7.83-8.50. Increasing the energy level in the feed can improve the quality of native chicken semen. The best feed to improve the quality of native chicken semen is feed with a metabolic energy of 2850 kcal/kg.